The Georgian logistics revolution: questioning seamlessness across the New Silk Road. (1st April 2019) - Gambino, Evelina
Abstract : Georgia, the post-Soviet republic in the South Caucasus, is undergoing its own logistics revolution. The government has pledged to complete by 2020 a spatial plan which aims to turn the country into a transit corridor for the New Silk Road. While this development is still underway, logistics zones - infrastructural hubs, free industrial zones (FIZ), manufacturing areas and malls - are emerging across the Georgian space. The New Silk Road initiative is promoting a perspective of a world without barriers, where logistics is not a means but an end: a world in which connectivity is productive in itself and where geopolitical reasoning has succumbed to geoeconomic calculations. This article aims at problematising this view by providing a grounded analysis of the workings of logistical spaces in Georgia, exploring the discourses, frictions and histories which engender capital accumulation within and beyond the Georgian space.